2019
DOI: 10.1002/hbm.24773
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral perfusion of the left reading network predicts recovery of reading in subacute to chronic stroke

Abstract: Better understanding of cerebral blood flow (CBF) perfusion in stroke recovery can help inform decisions about optimal timing and targets of restorative treatments. In this study, we examined the relationship between cerebral perfusion and recovery from stroke‐induced reading deficits. Left stroke patients were tested with a noninvasive CBF measure (arterial spin labeling) <5 weeks post‐stroke, and a subset had follow up testing >3 months post‐stroke. We measured blood flow perfusion within the left and right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
36
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(47 citation statements)
references
References 86 publications
10
36
1
Order By: Relevance
“…However, hypoperfusion in the peri-infarct area can remain for weeks after stroke 22 . In line with the results of the present study, the effects of stroke can also affect remote functional networks 26 , likely due to diaschisis (electrical, metabolic, or blood flow dysfunction in functionally connected areas remote from the lesion 55 ) or due to other signals leading to a widespread disconnection of brain networks 54 . In adult patients after stroke, hypoperfusion of anatomically intact areas can be seen up to a year after stroke 56 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, hypoperfusion in the peri-infarct area can remain for weeks after stroke 22 . In line with the results of the present study, the effects of stroke can also affect remote functional networks 26 , likely due to diaschisis (electrical, metabolic, or blood flow dysfunction in functionally connected areas remote from the lesion 55 ) or due to other signals leading to a widespread disconnection of brain networks 54 . In adult patients after stroke, hypoperfusion of anatomically intact areas can be seen up to a year after stroke 56 .…”
Section: Discussionsupporting
confidence: 90%
“…However, case studies of patients in the chronic phase after stroke report hypoperfusion in the lesioned hemisphere 22 , 24 , 25 and relate it to functional deficits, i.e. language problems 22 , reading deficits 24 , 26 , and phonological competence 26 .…”
Section: Introductionmentioning
confidence: 99%
“…In the absence of treatment, the results for all three perilesional rings revealed that perfusion in the damaged left hemisphere was lower than in the undamaged right hemisphere, consistent with previous findings (Boukrina et al, 2019;Brumm et al, 2010;Richardson et al, 2011;Thompson et al, 2017). Within the left hemisphere as well, tissue closer to the lesion was reduced in perfusion relative to more distant areas -for the 0-6mm ring compared to the 6-12mm ring, and for 6-12mm vs. 12-18mm.…”
Section: Discussionsupporting
confidence: 91%
“…Perfusion in perilesional rings is also consistently found to be abnormally low relative to undamaged homolog regions in the contralesional hemisphere (Brumm et al, 2010;Richardson et al, 2011;Thompson et al, 2017), though only marginally so in one study (Boukrina et al, 2019).…”
Section: Despite Variable Definitions Of How Far Perilesional Tissue ...mentioning
confidence: 87%
“…Hypoperfusion has previously been suggested to resolve over time in accordance with early behavioral recovery patterns [21][22][23]. However, case studies of patients in the chronic phase after stroke report hypoperfusion in the lesioned hemisphere [22,24,25] and relate it to functional deficits [22,24,26]. In the chronic stage after stroke, reductions of ipsilesional cerebral blood flow was correlated with infarct size in patients after left-hemisphere stroke, indicating sustained hypoperfusion in the affected hemisphere [20].…”
Section: Introductionmentioning
confidence: 95%